(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article presents an analysis of experimental work on the application of technology based on the use of Hatha Yoga means. The scientific feasibility of including complexes of yoga exercises in the educational process of physical education at the university is shown.